A report of six clinical cases of lowered blood cholesterol profile associated with supplementation with polypeptide K (Diabegard®), a polypeptide isolated from the seeds of Momordica charantia Linn - Yong, Yean Sirn; Lee, Cheng Lok; Ahmad, Zuraini; Abdullah, Muhammad Nazrul Hakim (Pharmacotherapy Group, Faculty of Pharmacy, University of Benin, 2014)
Purpose: To assess six patients with Diabegard® supplementation with reference to cholesterol profiles. Methods: We report the clinical courses of six individuals taking Diabegard® supplementation at 60 and 120 mg/day for 8 weeks. Results: Patients had a maximum of 52.13 % reduction in low-density lipoprotein (LDL) cholesterol, 47.67 % reduction in triglycerides and 35.78 % reduction in total cholesterol (TC) within 8 weeks of Diabegard® supplementation. Interestingly, high-density lipoprotein (HDL) cholesterol increased by approximately 23.29 %. Patients also had reduced readings for C-reactive protein (CRP) and homocysteine (with maximum reduction of 81.58 % and 57.41 % respectively). In some patients, these parameters were elevated prior to supplementation. Conclusion: These results suggest that supplementation of Diabegard® will improve patients’ cholesterol profile by reduction of LDL and TC. Patients also expressed lower CRP and homocysteine indicating reduced inflammation and reduction of cardiovascular diseases (CVD) risk. However, patients taking this supplementation are advised to seek medical consultation in monitoring their cholesterol and other biochemical profile levels.